Variable epidemic histories of hepatitis C virus genotype 2 infection in West Africa and Cameroon. - Pouillot, R; Lachenal, G; Pybus, O; Rousset, D; Njouom, R (2008)
It has recently been suggested that HCV genotype 2 (HCV-2) was more recently introduced to Cameroon (Middle Africa) than West African countries. In order to explore the relationships among HCV-2 strains from Cameroon and West Africa, and to estimate the epidemic history of each lineage, a recently-developed Bayesian evolutionary analysis approach was used. The estimated date of the most recent common ancestor (MRCA) of the Cameroon HCV-2 strains, 1630 (95% highest posterior density interval: 1470-1760) was slightly more recent than that of West Africa, 1540 (95% highest posterior density interval: 1380-1680). Estimates of epidemic history indicate significant differences between the two strains. HCV-2 appears to have spread relatively slowly within the West African population from 1630 to 1900, whilst the Cameroon lineages exhibit rapid, exponential spread from 1920 to 1960. This comparative genetic analysis indicates that Cameroon HCV-2 strains are derived from West African strains and that HCV-2 has undergone radically different epidemiological histories in the two regions.